Proceedings of the 2013 ACM Symposium on Principles of Distributed Computing 2013
DOI: 10.1145/2484239.2484262
|View full text |Cite
|
Sign up to set email alerts
|

Efficient distributed source detection with limited bandwidth

Abstract: Given a simple graph G = (V, E) and a set of sources S ⊆ V , denote for each node v ∈ V by L (∞) v the lexicographically ordered list of distance/source pairs (d(s, v), s), where s ∈ S. For integers d, k ∈ N∪{∞}, we consider the source detection,Solutions to this problem provide natural generalizations of concurrent breadth-first search (BFS) tree constructions. For example, the special case of k = ∞ requires each source s ∈ S to build a complete BFS tree rooted at s, whereas the special case of d = ∞ and S = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
140
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(140 citation statements)
references
References 31 publications
0
140
0
Order By: Relevance
“…Technical Discussion. Our key tool is a generalization of the (S, h, σ)-detection problem, introduced in [10]. 2 The problem is defined as follows.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Technical Discussion. Our key tool is a generalization of the (S, h, σ)-detection problem, introduced in [10]. 2 The problem is defined as follows.…”
Section: Introductionmentioning
confidence: 99%
“…Given a graph with a distinguished set of source nodes S, the task is for each node to find the distances to its closest σ ∈ N sources within h ∈ N hops (the formal definition is given in Section 2.5). In [10] it is shown that this task can be solved in h + σ rounds on unweighted graphs. The main new ingredient in all our results is an algorithm that, within a comparable running time, produces an approximate solution to (S, h, σ)-detection in weighted graphs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, many algorithms and lower bounds were given for computing and approximating graph distances in this setting [23,31,39,40,45,47,48,57,61,62]. Some lower bounds apply even for graphs of small diameter; however, these lower bound constructions boil down to graphs that contain bottleneck edges limiting the amount of information that can be exchanged between different parts of the graph quickly.…”
Section: Additional Related Workmentioning
confidence: 99%
“…At the heart of any routing protocol lies the computation of short paths between all possible node pairs, which is another This article is based on preliminary results appearing at conferences [32,34,35]. This work has been supported by the Swiss National Science Foundation (SNSF) fundamental challenge that occurs in a multitude of optimization problems.…”
Section: Introductionmentioning
confidence: 99%